Sobre H-hipersuperfícies compactas de N X R - Silva, Heloisa Frazão da (2011)
Consider F(N x R) the set of closed hypersurfaces M such that M C N x R) where N is a simply connected riemannian manifold with sectional curvature bounded above (KN ≤ -k2 < 0). Thereafter, with the aid of Hessian Comparison Theorem we show some inequalities for these submanifolds M С N x R with constant mean curvature HM.